Small Incision Lenticule Extraction (SMILE) versus Femtosecond Laser-Assisted In Situ Keratomileusis (FS-LASIK) for Myopia: A Systematic Review and Meta-Analysis. - Zeren Shen; Keda Shi; Yinhui Yu; Xiaoning Yu; Yuchen Lin; Ke Yao (PLoS ONE, 2016)
Purpose The goal of this study was to compare small incision lenticule extraction (SMILE) with femtosecond laser-assisted in situ keratomileusis (FS-LASIK) for treating myopia. Methods The CENTRAL, EMBASE, PubMed databases and a Chinese database (SinoMed) were searched in May of 2016. Twelve studies with 1,076 eyes, which included three randomized controlled trials (RCTs) and nine cohorts, met our inclusion criteria. The overall quality of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) working group framework. Data were extracted and analysed at three to six months postoperatively. Primary outcome measures included a loss of one or more lines of best spectacle corrected visual acuity (BSCVA), uncorrected visual acuity (UCVA) of 20/20 or better, mean logMAR UCVA, postoperative mean spherical equivalent (SE) and postoperative refraction within ±1.0 D of the target refraction. Secondary outcome measures included ocular surface disease index (OSDI), tear breakup time (TBUT) and Schirmer's 1 test (S1T) as dry eye parameters, along with corneal sensitivity. Results The overall quality of evidence was considered to be low to very low. Pooled results revealed no significant differences between the two groups with regard to a loss of one or more lines in the BSCVA (OR 1.71; 95% CI: 0.81, 3.63; P = 0.16), UCVA of 20/20 or better (OR 0.71; 95% CI: 0.44, 1.15; P = 0.16), logMAR UCVA (MD 0.00; 95% CI: -0.03, 0.04; P = 0.87), postoperative refractive SE (MD -0.00; 95% CI: -0.05, 0.05; P = 0.97) or postoperative refraction within ±1.0 D of the target refraction (OR 0.78; 95% CI: 0.22, 2.77; P = 0.70) within six months postoperatively. The pooled analysis also indicated that the FS-LASIK group suffered more severely from dry eye symptoms (OSDI; MD -6.68; 95% CI: -11.76, -2.00; P = 0.006) and lower corneal sensitivity (MD 12.40; 95% CI: 10.23, 14.56; P < 0.00001) at six months postoperatively. Conclusions In conclusion, both FS-LASIK and SMILE are safe, effective and predictable surgical options for treating myopia. However, dry eye symptoms and loss of corneal sensitivity may occur less frequently after SMILE than after FS-LASIK.